INSTAGRAM SOCIAL MEDIA MANAGEMENT IN DIGITAL BRANDING RADIO REPUBLIC OF INDONESIA PROGRAMA 3 - Azzahra, Muthia; Sari, Wina Puspita Sari; Soegiarto, Asep Soegiarto (JIKE : Jurnal Ilmu Komunikasi Efek, 2024)
The development of information and communication technology makes online media, especially social media, a medium utilized by Radio Republik Indonesia Pro 3 as a step for branding in the digital era. This study aims to determine the problem determination, planning, implementation and evaluation carried out by the Radio Republik Indonesia Pro 3 Instagram social media management team in managing Instagram social media in digital branding RRI Pro 3. The theory used in this research is the theory of the four stages of the public relations work process or four step public relations in which it includes some data collection, planning, implementation, and evaluation. The research method used is descriptive analysis with a qualitative approach. Data collection used in this research is by interview and passive participant observation. Based on the results of field research, it can be concluded that the RRI Pro 3 social media team in managing Instagram social media in digital branding uses a four-stage fact finding process, by finding valid data to determine Instagram content topics. Second planning, planning the type of content that will be created and uploaded on Instagram social media. Third Actions, implementing a team of content creators and admins who upload content. Fourth Evaluations assess the success of the team and the success of the content from the number of visitors to the official RRI website via Instagram and the number of insigh. Keywords: Social Media Management, Instagram, RRI Pro 3, Branding